(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
Dye waste is difficult to remove using conventional methods due to its high stability and resistance to biodegradation. However, scientific advancements have introduced alternative approaches, such as organometallic compounds, which can serve as catalysts and adsorbents. These compounds, particularly metal-organic frameworks (MOFs), possess a large surface area, flexible structure, high crystallinity, and adjustable pore size, making them highly effective in adsorption and photodegradation processes for dye wastewater treatment. This review discusses organometallic compounds, including Materials of Institut Lavoisier (MIL), Zeolitic Imidazolate Frameworks (ZIFs), and Porous Coordination Networks (PCNs), which have proven effective in absorbing certain dyes from water solutions. These MOFs, either alone or in composites with metal oxides, can significantly reduce dye contaminants in water. This review provides an in-depth exploration of the characteristics of organometallic compounds and analyzes their potential as adsorbents and photodegradation catalysts for the removal of dye contaminants from wastewater. Radicals produced through reactions between the valence and conduction bands of the catalyst material with H2O2 can oxidize dye pollutants. This review offers deep insights into the potential of organometallic compounds in dye wastewater treatment.